Exploring the structure and stability of cholesterol dimer formation in multicomponent lipid bilayers. Issue 16 (20th October 2016) - Bandara, Asanga; Panahi, Afra; Pantelopulos, George A.; Straub, John E.
Abstract : For 40 years, the existence and possible functional importance of cholesterol dimer formation has been discussed. Due to challenges associated with structural studies of membrane lipids, there has as yet been no direct experimental verification of the existence and relevance of the cholesterol dimer. Building on recent advances in lipid force fields for molecular simulation, in this work the structure and stability of the cholesterol dimer is characterized in POPC bilayers in absence and presence of sphingomyelin. The cholesterol dimer structural ensemble is found to consist of sub‐states that reflect, but also differ from, previously proposed dimer structures. While face‐to‐face dimer structures predominate, no evidence is found for the existence of tail‐to‐tail dimers in POPC lipid bilayers. Near stoichiometric complex formation of cholesterol with sphingomyelin is found to effect cholesterol dimer structure without impacting population. Comparison with NMR‐derived order parameters provide validation for the simulation model employed and conclusions drawn related to the structure and stability of cholesterol dimers in multicomponent lipid bilayers. © 2016 Wiley Periodicals, Inc. Abstract : The existence of cholesterol dimers has long been proposed to be important to the function of cholesterol in facilitating membrane domain formation and lipid–protein interaction. Molecular dynamics simulation is used to characterize the structure and stability of the cholesterol dimer, as well as its dependence on membrane lipid composition. The results support the existence of a variety of cholesterol dimer structures, the nature of which may be critical to our understanding of cholesterol's function.